2012
DOI: 10.1159/000338964
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis as Compared with Hemodialysis Is Associated with Higher Overhydration but Non-Inferior Blood Pressure Control and Heart Function

Abstract: Background/Aims: Fluid overload is an important factor causing cardiovascular complications in dialysis patients. We compared fluid status, blood pressure (BP) and heart function between peritoneal dialysis (PD) patients and hemodialysis (HD) patients. Methods: We recruited 94 PD and 75 HD patients in our hospital. Fluid status was assessed by bioimpedance spectroscopy. Home BP was recorded. Use of antihypertensives was retrieved by chart review. In each group, 39 patients received echocardiographic examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…We therefore speculated that dialysis therapy could partly decrease intraventricular energy loss, but cardiac structural diseases such as LV hypertrophy and myocardial fibrosis still contributed to the abnormally increased energy loss value; the unrelieved ventricular workload would create a feedback loop with the impaired LV mass index, which might help explain why long‐term dialysis therapy has no benefits for cardiac function, 23 and renal transplantation is not associated with substantial regression of the LV mass index in some patients with ESRD 24 . Although peritoneal dialysis treatment is characterized by continuous ultrafiltration, with better hemodynamic stability, 25 Yao et al 26 demonstrated that no difference in cardiac function was found between patients receiving peritoneal dialysis and hemodialysis. In our study, the patients receiving peritoneal dialysis had no significantly different degree of intraventricular dissipative energy loss compared to the patients receiving hemodialysis, and they had a similar regulated blood pressure level and LV mass index.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore speculated that dialysis therapy could partly decrease intraventricular energy loss, but cardiac structural diseases such as LV hypertrophy and myocardial fibrosis still contributed to the abnormally increased energy loss value; the unrelieved ventricular workload would create a feedback loop with the impaired LV mass index, which might help explain why long‐term dialysis therapy has no benefits for cardiac function, 23 and renal transplantation is not associated with substantial regression of the LV mass index in some patients with ESRD 24 . Although peritoneal dialysis treatment is characterized by continuous ultrafiltration, with better hemodynamic stability, 25 Yao et al 26 demonstrated that no difference in cardiac function was found between patients receiving peritoneal dialysis and hemodialysis. In our study, the patients receiving peritoneal dialysis had no significantly different degree of intraventricular dissipative energy loss compared to the patients receiving hemodialysis, and they had a similar regulated blood pressure level and LV mass index.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Yao et al compared the hydration state of 75 HD and 94 PD recipients in Taiwan using BIA in terms of mortality, blood pressure and cardiac function [ 24 ]. The analyzed PD group was, similarly to ours, younger and with less comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Their results are inconsistent with the considerably higher mean OH on HD found in our study. Nutritional state markers, dialysis vintage and mortality were not included in their analyses [ 24 ]. Other studies based on the use of different BIA tools and methodology also suggested more substantial OH affecting patients on PD [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Netherlands Cooperative Study on the Adequacy of Dialysis showed that systolic BP (SBP) is an independent predictor of mortality and an indicator of fluid overload in dialysis patients. In particular, two specific causes of hypertension are often present: increased arterial stiffness and fluid overload [8,9,10,11]. Hypertension and hypervolemia can result in an increase in the left ventricular (LV) afterload and may lead to an increase in LV wall thickness, although this condition alone fails to explain LV hypertrophy (LVH).…”
Section: Introductionmentioning
confidence: 99%